Etnobotani Tradisi Bebubus Suku Sasak: Kajian Etnografi Harmonisasi Manusia-Alam untuk Mewujudkan SDGs di Pulau Lombok - Putri, Hestiani; Putri, Luh Putu Sasmita Sridewi; Hadawiyah, Laelatun; Fitri, Ananda Desiani; Kusuma, Anindita SHM (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
The Bebubus tradition is a traditional medicine practice practiced by the Sasak tribe on Lombok Island that is still maintained to this day. This practice involves the use of various types of medicinal plants that have been passed down from generation to generation. This study aims to analyze the ethnobotanical perspective of the Bebubus tradition of the Sasak people on Lombok Island and determine the role of the Bebubus tradition in the harmonization of humans and nature to realize SDGs on Lombok Island. This research uses an ethnographic approach with the methods of in-depth interviews, participatory observation, and literature analysis. Information was collected from Bebubus practitioners, community leaders, and local residents in several villages on Lombok Island. The data obtained were analyzed qualitatively to identify the types of plants used, treatment methods, and cultural values associated with the practice of Bebubus. The results showed that the Bebubus tradition uses more than 11 types of medicinal plants that have various healing properties. This practice is not only beneficial for physical health, but also has deep spiritual and social values for the Sasak people. In addition, Bebubus contributes to the conservation of local biodiversity and supports the community's economy through the sustainable use of natural resources. The Bebubus tradition of the Sasak Tribe has great potential in supporting the achievement of SDGs, especially in terms of health and well-being (SDGs goal 3), especially in goal 3.9 reducing disease and death from hazardous chemicals and pollution. The preservation and development of Bebubus practices can be a model of sustainable harmonization between humans and nature, and enrich ethnobotanical knowledge in Indonesia.